Indonesia Faktor Penentu Kesenjangan Multigenerasi Dalam Tata Kelola Organisasi Sektor Publik Di Indonesia - Muhammad Khairul Anwar; Fuad Khoiril Mukminin; Brillyant Virechely Tarore; Arie Kumala Nisa’; Savia Melati (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2026)
The contemporary public sector workplace is increasingly characterized by employees from multiple generations working together. Differences in social and technological experiences shape varying levels of technological adaptation, work values, and communication styles. If not effectively managed, these differences may create generational gaps that hinder collaboration and reduce organizational performance. This research is designed to examine the roots of generational divides within public institutions and to evaluate how trust and loyalty toward the organization can serve as stabilizing forces that lessen the harmful consequences of such divides. This research adopts a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. Relevant studies published between 2016 and 2024 in journals indexed by Scopus and Google Scholar were screened and selected through clearly defined inclusion and exclusion standards. A total of 20 relevant articles were analyzed qualitatively through thematic classification and conceptual synthesis. The review focuses on three main dimensions shaping multigenerational dynamics: technological adaptation, work values, and communication styles. The findings reveal that generational gaps are most evident in technological adaptation, particularly in the use of digital systems and the speed of innovation adoption. Differences in work values such as preferences for flexibility, stability, and organizational commitment further intensify intergenerational tensions. Variations in communication styles also contribute to workplace misunderstandings. Organizational trust and loyalty are identified as key moderating elements that encourage intergenerational cooperation, support effective knowledge sharing, and increase employee involvement. The findings underscore the importance of inclusive human resource strategies aimed at advancing digital competencies, strengthening communication across age groups, and reinforcing trust within the organization.